Peak expiratory flow rate as a surrogate for forced expiratory volume in I second in COPD severity classification in Thailand - Chaicharn Pothirat (2018)
© 2015 Pothirat et al. Background: There are limited studies directly comparing correlation and agreement between peak expiratory flow rate (PEFR) and forced expiratory volume in 1 second (FEV1) for severity classification of COPD. However, clarifying the role of PEFR as a surrogate of COPD sever- ity classification instead of FEV1 is essential in situations and areas where spirometry is not routinely available. Purpose: To evaluate the agreement between FEV1 and PEFR using Global initiative for chronic Obstructive Lung Disease (GOLD) severity classification criteria. Materials and methods: This cross-sectional study included stable COPD patients. Both absolute values and % predicted FEV1 and % predicted PEFR were obtained from the same patients at a single visit. The severity of COPD was classified according to GOLD criteria. Pearson’s correlation coefficient was used to examine the relationship between FEV1 and PEFR. The agreement of % predicted FEV1 and % predicted PEFR in assigning severity categories was calculated using Kappa statistic, and identification of the limits of agreement was by Bland- Altman analysis. Statistical significance was set at P-value,0.05. Results: Three hundred stable COPD patients were enrolled; 195 (65.0%) male, mean age 70.4±9.4 years, and mean % predicted FEV1 51.4±20.1. Both correlations between the % predicted FEV1 and PEFR as well as the absolute values were strongly significant (r=0.76, P,0.001 and r=0.87, P,0.001, respectively). However, severity categories of airflow limitation based on % predicted FEV1 or PEFR intervals were concordant in only 179 patients (59.7%). The Kappa statistic for agreement was 0.41 (95% confidence interval, 0.34-0.48), suggesting unsatisfied agreement. The calculated limits of agreement were wide (+27.1% to -28.9%). Conclusion: Although the correlation between FEV1 and PEFR measurements were strongly significant, the agreement between the two tests was unsatisfied and may influence inappropriate clinical decision making in diagnosis, severity classification, and management of COPD.